1991
DOI: 10.3168/jds.s0022-0302(91)78364-1
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Fecal Flora of Calves Fed a Bacillus subtilis Concentrate

Abstract: Eighty-four Holstein calves were assigned at 2 d of age to one of three treatments: 1) control with no additives; 2) 10 g of a mixed microbial concentrate containing Lactobacillus acidophilus, Lactobacillus lactis, and Bacillus subtilis; or 3) 10 g of a B. subtilis concentrate. The microbial concentrates were mixed with milk replacer during the a.m. feeding. The milk replacer was offered twice daily at 5% BW per feeding; the reconstituted replacer contained 12.5% DM. Volume of replacer fed was based on initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
46
0
5

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 7 publications
9
46
0
5
Order By: Relevance
“…However, the practice of supplementing animal diets with DFM was originally based on the concept of delivering beneficial microorganisms to stressed animals with the expectation that the beneficial microorganisms would thrive in the gastrointestinal tract and prevent the establishment of pathogens (Weinberg et al 2007). It is therefore not surprising that most studies reporting positive effects of feeding DFM products have been conducted under conditions where the potential for stress has been high, including weaning and transporting of calves and steers (Schwab et al 1980;Jenny et al 1991). Kung (1998) summarized data from incoming feedlot cattle experiments where DFM were fed and reported an advantage of 10.7% in ADG and 5.4% in G:F with the feeding of DFM.…”
Section: Discussionmentioning
confidence: 99%
“…However, the practice of supplementing animal diets with DFM was originally based on the concept of delivering beneficial microorganisms to stressed animals with the expectation that the beneficial microorganisms would thrive in the gastrointestinal tract and prevent the establishment of pathogens (Weinberg et al 2007). It is therefore not surprising that most studies reporting positive effects of feeding DFM products have been conducted under conditions where the potential for stress has been high, including weaning and transporting of calves and steers (Schwab et al 1980;Jenny et al 1991). Kung (1998) summarized data from incoming feedlot cattle experiments where DFM were fed and reported an advantage of 10.7% in ADG and 5.4% in G:F with the feeding of DFM.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that B. subtilis has the potential to increase growth performance of pigs (Alexopoulos et al, 2004;Kritas and Morrison, 2005), chickens (Fritts et al, 2000) and calves (Jenny et al, 1991;Sun et al, 2010). Kritas et al (2006) reported that B. subtilis supplementation in ewe's feed increased average daily milk yield and milk fat and protein contents (Kritas et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…To date, only limited research relating to the dietary utilization of B. subtilis in ruminants has been completed (Jenny et al, 1991;Kritas et al, 2006), and studies have seldom evaluated the effect of feeding B. subtilis natto on ruminal microbial fermentation in dairy cows. Available results from in vitro studies have shown that B. subtilis natto has beneficial effects on the growth of some anaerobic microorganisms, such as Lactobacillus sp.…”
Section: Introductionmentioning
confidence: 99%
“…Reports on probiotic supplementation for calves have different results with respect to growing performance. Previous some papers reported beneficial effects of probiotics on animal growth (Abe et al, 1995;Timmerman et al, 2005;Frizzo et al, 2010), while others (Jenny et al, 1991;Higginbotham and Bath, 1993;AbuTarboush et al, 1996;Cruywagen et al, 1996) reported no effects. This discrepancy among the different studies may be related to several factors such as age at supplementation (Cruywagen et al, 1996) and environmental factors (Krehbiel et al, 2003).…”
Section: Resultsmentioning
confidence: 99%